2016
DOI: 10.1111/jmi.12432
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the artificial saliva storage on 3‐D surface texture characteristics of contemporary dental nanocomposites

Abstract: The aim of this study was to analyse the influence of the artificial saliva on a three-dimensional (3-D) surface texture of contemporary dental composites. The representatives of four composites types were tested: nanofilled (Filtek Ultimate Body, FUB), nanohybrid (Filtek Z550, FZ550), microfilled (Gradia Direct, GD) and microhybrid (Filtek Z250, FZ250). The specimens were polymerised and polished by the multistep protocol (SuperSnap, Shofu). Their surface was examined, before and after 3 weeks' exposure to ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…Our previous studies demonstrated that the corner frequency is found similar to average decay length, and hence to average grain diameter [28,29]. As a quick characterization tool, fractal analysis proved to be useful in studies of morphology and mechanical properties of various surface structures upon heat treatment [30][31][32], nanomechanical processing [33,34], in contact with body tissues and fluids [35][36][37][38]. Obtained results established a bridge between specific geometry of residual surface and its tribological and physical characteristics [39][40][41].…”
Section: Surface Texture Analysis From Afmmentioning
confidence: 78%
“…Our previous studies demonstrated that the corner frequency is found similar to average decay length, and hence to average grain diameter [28,29]. As a quick characterization tool, fractal analysis proved to be useful in studies of morphology and mechanical properties of various surface structures upon heat treatment [30][31][32], nanomechanical processing [33,34], in contact with body tissues and fluids [35][36][37][38]. Obtained results established a bridge between specific geometry of residual surface and its tribological and physical characteristics [39][40][41].…”
Section: Surface Texture Analysis From Afmmentioning
confidence: 78%
“…Similar discrimination can be made considering the results of fractal analysis shown in Table . As a rule (Ţălu et al, ), the most outer tissues, that is, the enamel and cementum, are found bifractal, whereas the dentin—monofractal. Bifractal characteristics correspond to structures with interpenetrating spatial arrangements on different length scales, for example regular clusters, while monofractal ones correspond to structures exhibiting spatial patterns of the first order only.…”
Section: Resultsmentioning
confidence: 97%
“…Recently, applications of nanotechnology in dentistry have been reported in order to improve tooth properties (Salerno & Diaspro, ; Ţălu et al, ; Ţălu, Yadav, Lainović, et al, ; Uskoković & Bertassoni, ). Enamel, dentin, and cementum as the hard tissue along with dental pulp are the main parts of every natural tooth.…”
Section: Introductionmentioning
confidence: 99%